Design and Evaluation of Mobile Based Self-Management System for Tuberculosis - Reza Safdari; Hajar Hasan Nejadasl; Sharareh Rostam Niakan-Kalhori; Bahram Nikmanesh (Tehran University of Medical Sciences, 2018)
Background and Aim: In recent years, tuberculosis is a major cause of illness and mortality due to infectious diseases. In fact, one of the reasons for increasing the incidence of tuberculosis is that it is often associated with HIV infection. The present study aimed to design and establish a mobile-based self-care system for controlling tuberculosis. Materials and Methods: The data required in this research for evaluating the information and designing the application were collected in two main steps: first, the data required in this research for information needs assessment and application design were collected by searching in library resources. A questionnaire was applied by physicians to validate and determine the significance of these elements.  Afterwards, based on information elements and the self-care, application was designed in the Android Studio environment. Results: Information elements and functional capabilities required by the program were determined. Web-based services as a system interface, not only provided the communication between the patient and the care provider, also allowed for patient monitoring and disease control. Then evaluation of the performance and performance of the program was done by doctors and software experts. The findings showed user satisfaction with the application. Conclusion: Monitoring of treatment electronically allows for less costly monitoring of the patient. In this study, we present a prototype of the relationship between self-care application and portal and its potential benefits, which will allow future studies to improve and add new capabilities.